Artérias coronárias em carnívoros neotropicais - Souza, Wilson Viotto de (2020)
The species of the Carnivorous order have a diverse and well-interpreted evolutionary history and play a fundamental role in the balance of ecosystems. A wide variety of these species is distributed across the Neotropical regions. Objective: to study the anatomy of the coronary arteries and their main ramifications in species of Neotropical animals and comparative inferences. To this end, the hearts of 72 specimens from five families were analyzed, collected dead on highways in the states of Minas Gerais, Rio de Janeiro and Rio Grande do Sul. The hearts were removed by sternothymia, the base vessels were dissected and stained as coronary arteries, later its branches were dissected with the aid of anatomical forceps and binocular stereoscope. The number of branches for the left ventricle was higher in dogs, while the branches for the right ventricle were higher in felids. In specimens from the Canidae, Mustelidade, Procyonidae and Mephitidae families, which are dominated by the left coronary and in individuals from the Felidae family with a balanced pattern. Coronary dominance seems to be available with a phylogenetic distribution of the species. Studies with examples of use from different regions are estimated to assess a relationship between coronary circulation and an evolutionary history in the Carnivorous order.